The Association Between Myasthenia Gravis and Higher Extrathymic Cancer Risk - Mohamed Khateb; Mai Abu Zant; Alaa Bsoul; Tomer Karny; David Yarnitsky; Shahar Shelly (Brain and Behavior)
ABSTRACT Background Myasthenia gravis (MG) is strongly associated with thymic tumors, but whether it is also associated with extrathymic cancers is debatable or whether MG can be considered a paraneoplastic disorder for extrathymic cancers. Methods This is a retrospective analysis of the MG cohort for 23 years' time (January 2000 to May 2023), extracting cancer rates with clinical, electrophysiological, and biochemical cancer associations and the effect of chronic medications. Results We identified 436 patients with MG and 3924 controls. The median age at symptom onset was 64 (5–93 years) for males and 54 (1–87 years) for females. MG symptoms at onset were recorded as ocular (60%), strictly bulbar (10%), or generalized (23%). Extrathymic cancer was found in 32% of MG patients. In 3%, thymic and extrathymic cancers co‐occurred. Compared to controls, neurology (12.2%, 159/1308), internal medicine (24.4%, 319/1308), or rheumatology (12%, 157/1308), MG patients had significantly higher rates of extrathymic cancers (p < 0.001). Compared to the rheumatology group, the cancer relative risk of 2.97, CI = 2.5–3.4. Furthermore, the prevalence of extrathymic cancers was significantly increased within the paraneoplastic time window, defined as ±5 years from cancer diagnosis to myasthenia onset (p < 0.01). Conclusion MG was significantly associated with an increased risk of extrathymic cancers, particularly within the paraneoplastic time window. These findings suggest that MG might potentially behave as a paraneoplastic disorder.